Effectiveness of telemedicine technologies for improving glucose control in patients with type 2 diabetes mellitus: a critical review - St. Jacques, Katherine (Kansas State University, 2021)
Uncontrolled diabetes mellitus is the seventh leading cause of mortality and the leading cause of blindness, kidney failure, and non-traumatic amputations in the United States. A high prevalence of type 2 diabetes mellitus (T2D) has placed a strain on health care systems due to costs associated with anti-diabetic medications as well as diabetes-associated morbidities and disabilities. Traditionally, medical care providers have prescribed lifestyle and medication changes during clinical face-to-face visits, however these visits are costly and are often not effective for producing desired changes in self-management techniques. Evidence shows that the current standard of care often fails to deliver on achieving evidence-based recommendations for glycemic control for patients with diabetes. Recent advancements in telemedicine technologies have emerged as promising platforms which can deliver diabetes management services while reducing unnecessary use of health care resources. Different technological approaches may vary with regard to patient glycemic control outcomes, and cost differences should be taken into consideration when selecting the technology that may provide the greatest overall benefit for the patient. Many newer glucometers have transmission capabilities, allowing these meters to link to smartphone Apps or websites. Patients can measure their glucose levels, share results with their healthcare team in real time, and talk over the phone or through video visits for medication or lifestyle interventions, all in a more expedient manner compared to traditional face-to-face visits. Remote monitoring of blood glucose levels by clinicians has been shown to be feasible and acceptable for patients with both type 1 diabetes mellitus (T1D) and T2D. With this background in mind, the aim of the current review was to evaluate the effectiveness of remote blood glucose monitoring compared to continuous glucose monitoring (CGM) for lowering HbA1c in adult patients with T2D. PubMed was searched for randomized controlled trials, clinical trials, and systematic reviews that included either remote blood glucose monitoring, CGM, or both, and individual interventions had to be longer than six weeks in duration. Studies also had to include adult patients with T2D and had to examine the outcome of change in HbA1c as the primary or secondary outcome of interest. Inclusion and exclusion criteria were determined a priori, and searches included a variety of search terms yielding 92 records, of which 27 articles met the inclusion criteria. Study findings suggested that both remote blood glucose monitoring and CGM are effective for reducing HbA1c in patients with T2D compared to controls. Both the absolute treatment means, and the average treatment mean differences suggest larger reductions in HbA1c in the remote blood glucose monitoring interventions as compared to the CGM interventions. In agreement with previous research, side by side comparisons of the included studies revealed a trend toward greater absolute reductions in HbA1c among all studies where patients had higher baseline HbA1c levels, frequent engagement with the clinical team for more timely and responsive management, as well as algorithm-based treatment plans. Future studies should include a comparison of feasibility, cost of care to implement the interventions, and cost savings to inform clinical decision making, thereby identifying the technology with the greatest overall benefit for patients with diabetes.
Keywords: Telemedicine; Type 2 diabetes mellitus; Remote blood glucose monitoring; Continuous glucose monitoring